Communications between General Practitioners and Consultants. Issue 5942 (23rd November 1974) - Long, Anne; Atkins, J. B.
Abstract : During 1972-3 a survey was made of the pattern of communication between 80 consultants in four hospitals in south-east England and 100 general practitioners in the catchment areas of these hospitals. This aimed to identify the factors which affect the efficiency of communication between these two groups and to look for ways of improving this. Face to face contact between consultants and general practitioners was extremely limited. The main communication links were the letters of referral and discharge, but even this form of communication had serious defects. Though most doctors were satisfied with communications in general the evidence suggested ways of improving communication between consultants and general practitioners, such as encouraging domiciliary visits where both doctors are present and consultant sessions in health centres, but that any innovation in this field could only be successful if the attitude of the consultants and general practitioners were in harmony with the new venture.